Estudio de prefactibilidad para la instalación de una planta de elaboración de cerveza artesanal Super Premium tipo Ale - Manco Fernández, Alonso Rodrigo (2018)
This investigation work aims to determine the feasibility of installing an Ale super Premium craft beer production factory, targeted to attend the zone 7 of Metropolitan Lima. The main characteristics of this beverage, as well as the elements that make it distinctive from the ones already in the market, are detailed through the following chapters. The market research shows that the current market size rises up to 390 965 liters or S/.5 082 545, because of the fact that consumers would be willing to pay up to S/.13,00 per bottle of 330 ml. Also, the forecasted demand for the years of the project life (2016-2020) has growth potential, based on the rapid growth of the sector. As a consequence, by 2020 it is expected that the company has 57% of market share, which is equivalent to 246 878 liters or S/.7 486 743(excluding taxes). The factory will be based in Lurín, because of the land cost, the closeness to the market, the availability of water and electric power resources, among other micro and macro localization factors detailed ahead. The factory will have an area of 2 400 m2 and a maximum production capacity of 250 800 liters. Within the years of the project life, there are no plans to reach that maximum capacity, which will permit to respond to any unexpected demand fluctuation. The initial investment of the project rises up to S/.3 575 462 and it would be funding by a bank (70%) and by the stakeholders (30%). The project is profitable since it has a positive economic NPV, as well as, a positive financial NPV; it has an economic IRR of 47% and a financial IRR of 91%; a B/C ratio higher than the unity, and both economic and financial recovery period of less than 3 years.